Conservation Directory 1992 - National Wildlife Federation, Washington, DC.; National Wildlife Federation, Washington, DC. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1970)
This list of natural resource use and management organizations in the United States and Canada is supplemented with indices to their major periodical publications and to individuals named in the directory. Sections of the directory deal with agencies of the U.S. government; organizations and commissions with international, national, regional, and interstate interests and responsibilities; and with government agencies and citizen groups with interests in one state. There is a separate Canadian section. Brief descriptive notes outline the interests, objectives, and responsibilities of most organizations listed. Names and addresses of officers are included. An appendix lists names and addresses of fish and game commissioners and directors in each state and territory of USA and Canada. (AL)
Availability: The National Wildlife Federation, 1412 16th St., N.W., Washington, D.C. 20036 ($1.50).
Microfiche.
Keywords: Administrative Agencies; Community Organizations; Directories; Fisheries; Natural Resources; Wildlife Management